Enhancing Self-Error Correction in English Writing of Thai Undergraduate Students through Online Concordances and Correction Symbols - Sinturat, Thitapa; Kosashunhanan, Krishna; Rungswang, Atichat; Sittironnarit, Sita; Worakul, Kulsiri (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this research were 1) to develop students’ self-error correction in English writing by using online concordances and correction symbols; 2) to investigate the grammatical errors that were corrected after using the online concordances and correction symbols; and 3) to explore the students’ satisfactions towards using the online concordances and correction symbols in self-directed learning. The research design was one group pretest and posttest. The sample group was 35 second-year students majoring in English for Communication, Faculty of Liberal Arts at Rajamangala University of Technology Thanyaburi. All the 35 students were studying the course of English Structure for Writing Development. Convenient sampling was employed in this research. Also, the students were divided into three groups of English language competency including above average, average and below average. The students were assigned to write three types of writing: narrative, descriptive and comparison-contrast. There were three raters checking through holistic assessment and grammatical errors were categorized at word level. The research instruments were an online concordance of Lextutor, correction symbols, pretest and posttest, grammatical error-correction tasks, questionnaire (5-point rating scale) and in-depth interview. The statistics used in this research were percentage, mean, standard deviation, and the correlation coefficients among three raters. The results revealed that in three types of writing the correlation coefficients among three raters are high with statistical significance at the level of .05. The average of posttest scores was significantly higher than pretest scores at the level of .05. The students’ attitude for self-directed learning through using an online concordance line in English writing was at a high level. The posttest score was higher than the pretest score at .05 statistical significance level and perceived the corpus approach as beneficial to the development of their English writing skills.